Análisis de las ventajas competitivas del sector floricultor de Colombia y Holanda en periodo 2012-2017 (2018)
The Colombian floriculture sector becomes one of the most competitive within the productive sectors of the world, due to the advantages that Colombia has which are different climates and its topography, which have allowed the floriculture sector to offer to the world a great variety of flowers of excellent quality. However, Colombia has not managed to overcome of its great competitor Holland, since it has been based exclusively on its endowment of natural resources. For its part, Holland is the undisputed world leader in the floriculture sector, this has been achieved thanks to its great technological advances in the management of crops, great government support and innovation in their products.